In Vitro Studies of Capreomycin Sulfate Release from Polyethylcyanoacrylate Nanoparticles - Burkeev, M.Zh.; Zhaparova, L.Zh.; Tazhbaev, E.M.; Zhumagalieva, T.S.; Sayed, I.Ali; van Herk, Alex M. (Springer, 2013)
The potential use of polyethylcyanoacrylate as a carrier for the antituberculosis agent capreomycin sulfate was demonstrated. In vitro studies addressed the release of capreomycin sulfate from polyethylcyanoacrylate nanoparticles and degradation of the polymer.
Keywords: polyethylcyanoacrylate nanoparticles; capreomycin sulfate; drug release; degradation; erosion